Community Pharmacists’ Attitudes and Professional Practice in Relation to the Patient Safety Incidents - Marinkovic, Valentina; Stojkovic, Tatjana; Zekovic, Milica; Tasic, Ljiljana; Krajnovic, Dusanka (Indian Journal of Pharmaceutical Education and Research, 2020)
Background: Medicines dispensing is an error-prone activity, therefore potentially jeopardizing patient safety. This study aimed to assess the community pharmacists’ attitudes towards the causes of dispensing errors and preventive measures, as well as their practice in incidents reporting. Materials and Methods: A cross-sectional survey was performed by distributing an adopted and validated questionnaire to a nationwide sample of community pharmacists in Serbia. The questionnaire included sections related to the participants’ socio-demographic characteristics, their attitudes towards factors causing dispensing errors and corrective actions, as well as their practice in reporting. Statistical analyses were conducted using SPSS Statistics software ver. 21.0. The associations between categorical variables were analyzed using Chi-square test. Results: The study included 1,004 participants, mainly female (94.9%), with the mean age 40.9±9.9 years and mean work experience 14.3±10.0 years. More than a third of the participants (35.4%) indicated an increasing risk of dispensing errors. The main causes included illegible prescriber‘s handwriting (44.3%) and interruptions during dispensing (39.2%), while the major corrective actions were providing pharmacists with education in clinical pharmacy (71%) and reducing the interruptions during dispensing (63.9%). The majority of respondents (85.2%) stated that they routinely reported dispensing incidents. However, even 16.5% of them admitted to having fear sometimes or always. Additionally, only 58.1% of participants would use voluntary dispensing error reporting system. Conclusion: Serbian community pharmacists are aware of the existing risk in medicines dispensing and the corrective actions identified should be put into practice so as to manage them prospectively. Although the results indicate good practice in incidents reporting, conducting tailored educations and building of safety culture is necessary to improve patient safety.
Keywords: Dispensing errors; Community pharmacy; Patient safety; Pharmacists’; attitudes; Risk management; Systems approach